Investigating the Diagnostic and Risk Factors for Enterocolitis in Children with Hirschsprung’s Disease - Askarpour S.; Javaherizadeh H.; Peyvasteh M.; Mohammadi A.; Soma Seyedsalehi S. (Acta Medica Bulgarica, 2025)
This study aimed to identify the clinical risk factors associated with Hirschsprung-associated enterocolitis (HAEC) in children with Hirschsprung’s disease (HD).